Primary Calvarial Meningioma- Repaired by Acrylic Bone Cement: A Case Report - Talha, Khandaker Abu; Hossain, ATM Mosharef; Asaduzzaman, Khan; Wahed, Amer; Selina, Farhana; Henry, Paul T (TAJ: Journal of Teachers Association, 2010)
We present a lady with scalp swelling and headache. CT scan of brain showed a right parietal bony lesion without any dural or parenchymal invasion. Tumour was removed. Bony gap was repaired by acrylic bone cement. Post operative recovery was uneventful. Biopsy report of tumour was primary calvarial meningioma. This is a very rare type of CNS tumour. Only very few cases were reported before. TAJ 2010; 23(1): 80-83